Research on Aesthetic Education Literacy Cultivation Pathways for Preschool Education Teacher Candidates at Regional Undergraduate Institutions under the "Aesthetic Education Immersion Initiative" - Lin, Yang (Education Insights, 2026)
Aesthetic education literacy has emerged as a critical professional literacy for teacher candidates. This study examined 110 Preschool Education teacher candidates at University A in Baoshan City, investigating their aesthetic education competencies across five dimensions: aesthetic perception competency, cultural comprehension competency, aesthetic creation competency, aesthetic expression competencies, and aesthetic education competency. Findings revealed that Preschool Education teacher candidates demonstrated strong nature appreciation and everyday humanistic understanding, while artistic analysis required enhancement; exhibited high cultural confidence and multicultural conceptual understanding, yet needed deeper comprehension of artwork-culture relationships; showed excellent artistic engagement and emotional responsiveness with technical proficiency, though analytical and creative skills needed improvement; displayed high exploratory enthusiasm with foundational comprehensive creation abilities, while practical application required further development; and demonstrated "advanced pedagogical concepts, limited theoretical knowledge, insufficient practical implementation." Recommendations include leveraging Preschool Education arts curricula as primary platforms for transformation from "skill-based" to "competency-integrated" approaches; establishing "disciplinary aesthetic education" principles implementing educational practices according to aesthetic principles; developing project-based learning (PBL) aesthetic education activities emphasizing student-centered, problem-focused, outcome-oriented methodologies; and reforming aesthetic education assessment mechanisms through process-oriented portfolio evaluation focusing on embodied participation and developmental processes, incorporating aesthetic practice into comprehensive teacher candidate assessment frameworks.